(untitled) (Journal of Hama University, 2024)
The aim of this research, in general, is to identify the most important problems facing strawberry growers within the greenhouses in the Talkalakh region, and therefore the factors responsible for explaining the largest percentage of the total variance using the exploratory factor analysis using the principal components method, and the orthogonal rotation of the axes by the Varimax method, and a questionnaire was used. Traditional, in which the primary data was collected through a personal interview of a random sample of (292) farmers, and the data was analyzed statistically by the spss statistical analysis program, where the results of the analysis showed the presence of three factors with a root greater than one for each of them, which together explained 72.668% of the total variance. These factors are the problems of providing production requirements, marketing problems and the state’s lack of interest in this crop, which explained (28.072%, 23.390%, 21.206%) of the total variation for each of them, respectively. The study concluded with a number of recommendations, the most important of which is providing production requirements at state-subsidized prices and monitoring their quality, providing a financing service (loans) for solar pumps for strawberry farmers without any interest, and establishing an association of strawberry growers that provides facilities such as setting a unified price policy that prevents merchants from controlling the price, accelerating Implementing the state-supported agricultural insurance project on greenhouses.